If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -16 = 47 Reorder the terms: -16 + 7n = 47 Solving -16 + 7n = 47 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 7n = 47 + 16 Combine like terms: -16 + 16 = 0 0 + 7n = 47 + 16 7n = 47 + 16 Combine like terms: 47 + 16 = 63 7n = 63 Divide each side by '7'. n = 9 Simplifying n = 9
| 5x+22=2(x-4) | | 6n-13=41 | | 6n-13=61 | | 5n+10=25 | | x-3+x+x+2=35 | | (n-3)*9=90 | | 65+10x=6 | | x-1+x+x+3=32 | | (n-5)*6=48 | | 3(7x-1)=5(3x+3) | | 25=2c-9 | | 9x-4(3x-2)=4 | | 5x=2(x+30) | | 3b+15=27 | | m+2=15 | | 9x-19=7x+11 | | 15x^3+25x^2-60x= | | 8t-11=5t+19 | | -2(18-3t)=7y+2y | | -(5y+2)-(-4y-8)=1 | | 4-x=-5 | | 2(x+30)= | | 6n-2=14 | | 52=(3x+6)+(6x+22) | | 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 |